FACTORS EFFECTING THE ADOPTING OF DIETARY DIVERSITY FORNUTRITIONAL SECURITY AMONG RURAL FARM WOMEN INWARANGAL, TELANGANA: A DESCRIPTIVE RESEARCH - KHUSHBOO YADAV, M. PREETHI, M. PRASUNA, APARNA KUNA, AMTUL WARIS and D. SRINIVASA CHARY (The Journal of Research, PJTSAU, 2026)
Dietary diversity served as a practical proxy for the micronutrient adequacy of diets consumed by rural farm women. Thefarm women remained disproportionately vulnerable to undernutrition despite its central role in agricultural production and householdfood provisioning. The present study was conducted among 30 rural farm women of reproductive age group (15 – 49 years)Warangal district village. The results revealed that majority of the respondents belonged from a selected village in (56.67%) middleage group followed by young (30.00%) and old (13.33%) age group. The category unveiled the respondents profile consisted ofmajority (43.33%) with Schedule caste followed by 33.33 per cent of OBC respondents and 16.67 per cent were from generalcategory whereas only 6.67 per cent belonged to schedule tribes (ST) accounted the least. The family type of respondentsbelonged to nuclear (60.00%) and (40.00%) joint family type. While the factors affecting them to attain dietary diversity showed theeconomic constraints and agricultural as well as household work load hindered the most. Poor market assess, low decisionmaking authority, poor nutritional knowledge and low livestock ownership were some more prominent contributors for theirperceived constraints. The bottom most constraints ranked by the respondents were limited nutrition contact, limited homesteador kitchen garden followed by social norms and poor sanitation and unsafe water. The perceived constraints highlight the diverseyet important issues which rural women encounter in her highlighted life.